Fenomena Trending Topic Seksual Twitter Terhadap Persepsi Mahasiswa - Resyla Cheril; KYS Putri (UMSU, 2022)
AbstractThe trending topic of sexuality on Twitter which often rises to become the number one search is sometimes invites some teenagers to look out of curiosity. This study aims to determine the perceptions of students, especially UNJ communication science students, on the phenomenon of trending topics of sexuality and their impact on social media Twitter. In this study, the researcher uses a qualitative approach, in order to examine social settings from an insider's perspective and produce a description and analysis of the context. The researcher also uses hermeneutic phenomenology which explains that this research is oriented to life experience and tries to interpret its meaning. The results of this study are that some students feel uncomfortable with the emergence of trending topics that lead to sexual matters. Sexual contents is not a good thing to be consumed even to be spread in public spaces. Content like this sometimes makes them nervous because the impact of this trending topic can make other people feel curious to imitate and indicate free sex on teenagers.Keywords: new media, social media, sexual behavior